CURRICULUM MANAGEMENT IN IMPROVING THE QUALITY OF LEARNING - Hasanah, Uswatun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The development of the quality of education is significant in shaping thecharacter of students who master science. One aspect that influences thesuccess of education is the curriculum aspect. This study aims to determinecurriculum management in improving the quality of learning, to understandthefunctionsofcurriculummanagement,andcurriculumevaluationatMadrasah Aliyah Nurul Jadid. This research includes field research using aqualitative approach to data collection. The author uses interview, observation,anddocumentationmethods.Dataanalysistechniquesusediligentobservation techniques and checking with colleagues through discussion. Thestudy results a show that curriculum planning at Madrasah Aliyah Nurul Jadidinvolves school supervisors, existing stakeholders, and student guardians.Curriculum planning is carried out at the beginning of the new school year.Procedures in curriculum management carry out curriculum organization.Implementation of the curriculum is carried out by all teachers in the form oflearning activities and extracurricular activities. Curriculum evaluation iscarried out by direct monitoring by the deputy head of curriculum, thenreported to the school principal. In addition, each teacher is also required tomake a report on teaching activities for one year. The results of the evaluationwill be used as material for consideration in curriculum planning; then, afollow-up plan will be carried out for the year next.